(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
The ancient Dabusia city ruin, as we know, is located at the crossroads of the Great Silk Road. It is formed from three parts, like theconstruction of traditional cities of Central Asia: Ark(citadel), Shahristan and Rabat part. This article discusses some aspects of Dabusiya Castle on the Great Silk Road.